(untitled) (AYUSHDHARA, 2018)
Ayurveda has been created by Lord Brahma and descended to earth in the form of Trisutra. This gets ramified into Astanga Ayurveda. The 8 branches are Shalya, Shalakya, Kayachikitsa, Bhootavidya, Koumarbhritya, Agadatantra, Rasayantantra, Bajikaran Tantra. Susruta Samhita though covers all the 8 branches of Astanga Ayurveda but it emphasis more on Shalya Chikitsa. Kayachikitsa is more elaborarately dealt by the father of medicine Charak in his book Charak Samhita. The Kayachikitsa related topics are all scattered in Susruta Samhita and make it hard for the readers to find out their topics. So, for the convenience of the reader and easily accessible and handy, the present work has been carried out. In Susruta Samhita Kayachikitsa has total 46 chapters of related topics. Sutrasthan contain 5 chapters, Nidansthan contain 7 chapters, Sharir sthan contain 3 chapters, Chikitsa Sthan contain 9 chapters, Kalpa Sthan contain 2 chapters and Uttar Tantra contain 20 chapters. Compiling the scattered topics of Kaya Chikitsa available in Susruta Samhita will make the reader easy to choose its topic of interest in Susruta Samhita regarding the Kaya Chikitsa related topics and it also helps further in research works.